Judul Pelatihan Penerapan Biopori untuk Membuat Kompos dari Sampah Organik di Desa Tlogopakis, Kabupaten Pekalongan - Mustaqim, Mustaqim; M, Isradias; Yunus, Muhamad; Ikhwan, Ikhwan; Widiyaningsih, Nanda; Umisara, Elinda (LPPM Universitas Muhadi Setiabudi, 2026)
The community service program of the Faculty of Engineering and Informatics, Universitas Pancasakti Tegal, was implemented in Tlogopakis Village, Pekalongan Regency, addressing environmental issues through training on the application of biopores as a solution for organic waste management. This activity aimed to increase the awareness of the Tlogopakis Village community regarding the importance of environmentally friendly waste management while utilizing organic waste for compost production. The methods employed included socialization sessions, demonstrations of biopore hole construction, and hands-on practice assistance. The results showed increased community participation in managing organic waste as well as the creation of effective water infiltration facilities. This program is expected to be sustainable and serve as a model for other villages.